Promoting Intellectual Property Monetization in Developing Countries : A Review of Issues and Strategies to Support Knowledge-driven Growth - Ghafele, Roya (World Bank, Washington, DC, 2012)
This paper outlines and evaluates several intellectual property monetization strategies available to patent holders in developing countries that help generate domestic innovation and knowledge-driven growth by promoting more active technology markets. Based on a review of World Intellectual Property Report indicators, the patent ownership gap between a sample of developed and developing countries has narrowed gradually for more technologically-sophisticated developing countries. However, based on complementary International Monetary Fund Balance of Payments data, the patent commercialization divide (as indicated by licensing income) has been widening. The paper argues that patents, and all forms of intellectual property, are an enabling mechanism rather than a defensive right: an intangible asset class that can be proactively nurtured and managed for greater value extraction to stimulate knowledge-based entrepreneurship and growth in developing countries. The paper presents multiple case studies of alternative monetization strategies to address the commercialization divide. These strategies range from private, market-driven options to those requiring a greater amount of public policy support: from patent securitization and patent exchanges (focusing on the United States-initiated Intellectual Property Exchange International and the Shanghai Silicon Intellectual Property Exchange), to the strengthening of technology transfer and commercialization infrastructure (focusing on the experience of the Association of University Technology Managers and Taiwan, China's Intellectual Property Rights Institute), to patent litigation support (including South Korea's support of patent infringement lawsuit costs for small and medium enterprises). The paper also highlights areas where further policy research would be helpful.